Menggali Nilai-Nilai Pada Tarian Gawi Dari Aspek Sosial Budaya Kelurahan Wolojita, Kecamatan Wolojita, Kabupaten Ende - Senggo, Elisabeth; Gisela Nuwa; Abbdullah Muis Kasim (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Gawi dance is the wealth of the ancestors of the Ende Lio tribe, which existed since the time of the ancestors, until it was passed down from generation to generation until now. In this study, we wanted to find out what values ??are contained in gawi, and wanted to know the existence of the gawi dance. The type of research used is a qualitative research. The approach used in this study is a qualitative approach. The main subjects in this study are traditional leaders (mosalaki), poetry singers (ata sodha), community leaders. Furthermore, data collection techniques are carried out by conducting interviews and documentation.From the results of this study, the values ??contained in the Gawi dance, such as regius values, aesthetic values, togetherness values ??and the existence of the Gawi dance, have existed since the time of the ancient ancestors, and have been passed down from generation to generation to the next generation. Its existence only exists in Ende Regency. From the results of the study, it can be concluded that the existence of the gawi dance for the Wolojita people is very attached to the community itself. Thus, it can be said that it is still very close and cannot be lost from the life of the Wolojita people, especially the people of Ende Regency.